2009
DOI: 10.1111/igc.0b013e3181a1c6df
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Patients With Locally Advanced Cancer of the Cervix Treated With Neoadjuvant Chemotherapy Followed by Radical Surgery

Abstract: New concept of downstaging locally advanced cancer of the cervix (LACC) with neoadjuvant chemotherapy (NACT), to make it resectable, is of great interest and needs to be explored. This is a retrospective study of 56 LACC patients. Efficacy of NACT was measured in terms of optimal pathological response (OR). Percentage of patients who needed adjuvant radiotherapy and disease-free interval at 2 years was evaluated. Clinically, 49 patients (87.5%) responded well to NACT with TIP regimen (paclitaxel, ifosfamide, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Cisplatin and ifosfamide are the most effective drugs in monotherapy in cervical cancer patients. The three-drug combination of paclitaxel, ifosfamide and cisplatin (TIP) is currently most often used in cervical cancer patients [25][26][27][28]. There are more complete responses in early stage cervical cancers, but the interval between cycles is from 21 to 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin and ifosfamide are the most effective drugs in monotherapy in cervical cancer patients. The three-drug combination of paclitaxel, ifosfamide and cisplatin (TIP) is currently most often used in cervical cancer patients [25][26][27][28]. There are more complete responses in early stage cervical cancers, but the interval between cycles is from 21 to 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…16 A retrospective study of NAC for patients with cervical cancer also revealed no recurrence among patients with the optimal pathological response. 17 From 1997 through 2006, TUAC with cisplatin was administered at our institution in combination with paclitaxel or etoposide for patients with cervical cancer consisting of adenocarcinoma or small cell carcinoma, respectively. A total of 20 patients (14 patients with squamous cell carcinoma, 5 patients with adenocarcinoma, and 1 patient with small cell carcinoma) who achieved pCR were alive for more than 7 years after treatment, without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[6] In 1999, five large prospective randomized trials performed by the Gynaecologic Oncology Group (GOG), Radiation Therapy Oncology Group (RTOG) and the SouthWest Oncology Group (SWOG) demonstrated significant survival advantage and superiority in reducing risk of death by 30-50% in cisplatin-based therapy given concurrently with pelvic radiotherapy when compared to either radiotherapy alone or radiotherapy in concurrent with nonplatinum containing chemotherapy. [7][8][9][10][11] It was stated that cisplatin-based chemoradiotherapy also decreased the relative risk of recurrence and the mortality. Based on the results of these five randomized clinical trials, which consistently showed improved survival in patients treated with cisplatin-based concurrent chemoradiotherapy the National Cancer Institute (NCI) of the United States announced that "Strong consideration should be given to the incorporation of concurrent cisplatin-based chemotherapy with RT in women who require radiation therapy for treatment of carcinoma cervix" in 1999.…”
Section: Introductionmentioning
confidence: 99%